"Through variously tinted cosmopolitan glasses": Vernon Lee's travel writing of the British Isles. Issue 4 (2nd October 2019) - Murray, Alex
ABSTRACT: Vernon Lee is regularly upheld as a model of late-Victorian cosmopolitanism, with her travel writing, in particular that dealing with Italy, displaying an openness to other places and cultures. Yet, as this essay argues, there is in Lee's model of topographical writing a neglect of the people who live and dwell within landscapes. Examining in detail her critically neglected travel writing of the British Isles, published between 1899 and 1916, the essay surveys her hostility towards English landscapes and towards the forces of industrial modernity that shape them. From her antipathy to London to her celebration of the empty landscapes of Northern England, Lee's travel writing suggests her cosmopolitanism raises ethical questions about her relationship to those people and places that do not accord with her aesthetic taste.